ANALISIS KONVERSI LAHAN SAWAH DI KOTA SOLOK - Mardianto, . (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2018)
Agricultural land conversion occurs mostly in big cities in Indonesia and also occurs in small villages and towns on a small scale but not much has been done by the study. This study was linked to detect factors affecting land conversion in Kota Solok. This research was conducted by survey method. Sampling is done by simple random sampling with balanced amount. The data collected in this study includes primary data and secondary data. The analysis is done by description using percentage of respondent's level of achievement (tcr). The result of the analysis shows that the conversion of paddy fields in Solok City is mostly done by individual buyers, the internal factor which has the greatest effect on the conversion of paddy fields in Solok City is the economic condition, while the external factor is caused by the population growth and the policy caused by the weakness of policy control which government apparatus.